IDENTIFIKASI Lernaea sp. YANG MENGINFEKSI IKAN ARWANA IRIAN {{Scleropagesjardinii (Saville-Kent, 1892)} DI MERAUKE, JAKARTA, BOGOR DAN DEPOK - Dikry N Shatrie; Kurniasih Imamudin; Wisnu Nurcahyo; Triyanto Triyanto (BERITA BIOLOGI, 2011)
Lemaea spp. is very important fish ectoparasites because it spreads all over the world and its economic importance has increased due to numerous epizootics occurrence among the most important farmed fish; and has wide host range. Lemaea sp. has been infected not only the family Cyprinidae and Characidae but also in Osteoglossidae family, such as Red Arwana [Scleropagesformosus) in Malaysia and Arwana fish {Scleropagesjardinii (Saville-Kent, 1892)) in Irian.The objective of this study was to identity Lernaea sp. often attacked Arwana irian fish as a precautionary measure the spread of infection, especially on Arwana irian fish. Arwana irian fish were collected from Merauke, Jakarta, Bogor and Depok, 10 infected fish per area. Found Lernaea sp. fixed in glutaraldehyde for morphology study. Based on morphological charactheristic, there were six different Lemaea sp. attacked Arwana irian fish. They are Lemaea cyprinacea, L. devastatrix, L. lophiara, L.oryzophila, L. papuensis and Lemaea n sp. Lemaea n sp. was considered as a new species due to different variation of holdfast organ.